Constructs in Contexts Models of Contextualizing Adventist Theology - Wogu, Chigemezi-Nnadozie (2019)
As Seventh-day Adventism mirrors the global trends in world Christianity, the contextualization of its message has taken various forms, even as this formerly North American movement continues its global spread apace. It is therefore appropriate to ask in what ways Adventists have contextualized their message. Using a historico-contexual perspective, I analyze mainly academic works of Adventist theologians and missiologists that discuss ways Adventism has been adapted to a very broad audience.
Keywords: Seventh-day Adventism; Contextualization; Mission; Model; Theology